Political Legacy of Administrative Succession - Welsh, M. Ann; Dehler, Gordon E. (Academy of Management Journal, 1988)
The article examines the influence of political activity during executive succession on post-succession outcomes. A discussion is presented about the influence of an organization's resource environ...